Abstract Filipe+Braumann WNI 2008 - Filipe, Patrícia A. (2009)
Oral communication at the international conference Workshop on Nonparametric Inference (Coimbra, Portugal, June 2008). Web page: http://www.mat.uc.pt/~wni2008/ Study and parameter estimation for one and several trajectories (including bootstrap methods) of stochastic differential equation models for the growth of individual animals in randomly fluctuating environments.